2015
DOI: 10.1042/bst20150107
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic signatures linked to macrophage polarization: from glucose metabolism to oxidative phosphorylation

Abstract: Macrophages are present in a large variety of locations, playing distinct functions that are determined by its developmental origin and by the nature of the activators of the microenvironment. Macrophage activation can be classified as pro-inflammatory (M1 polarization) or anti-inflammatory-pro-resolution-deactivation (M2), these profiles coexisting in the course of the immune response and playing a relevant functional role in the onset of inflammation (Figure 1). Several groups have analysed the metabolic asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 45 publications
1
61
0
Order By: Relevance
“…Further studies will delineate the processes of selective targeting of proteins for S-NO modification and its effect on functional activity of the proteins. It is intriguing to note that (a) phagocytes activation and a decline in fatty acid metabolism where both of which were not spared from S-NO modification were differentially regulated in HF; (b) recent studies have indicated that upregulation of glucose metabolism promotes proliferation and activation of proinflammatory macrophages [38]. Our findings provide the first indication that a metabolic shift potentially contributes to proinflammatory state in progressive HF, to be verified in future studies.…”
Section: Discussionsupporting
confidence: 56%
“…Further studies will delineate the processes of selective targeting of proteins for S-NO modification and its effect on functional activity of the proteins. It is intriguing to note that (a) phagocytes activation and a decline in fatty acid metabolism where both of which were not spared from S-NO modification were differentially regulated in HF; (b) recent studies have indicated that upregulation of glucose metabolism promotes proliferation and activation of proinflammatory macrophages [38]. Our findings provide the first indication that a metabolic shift potentially contributes to proinflammatory state in progressive HF, to be verified in future studies.…”
Section: Discussionsupporting
confidence: 56%
“…58 Inhibition of glycolysis attenuates the adipocyte release of CCL2 in response to TNF-a or lipopolysaccharide, 59 demonstrating the connection between metabolism and inflammation. Pro-inflammatory (M1) macrophages rely on glycolysis for their metabolic demands.…”
Section: Atm Cytokines Productionmentioning
confidence: 99%
“…In particular, upon IFNγ/LPS stimulation, the expression of PFK2 shifts from the liver isoform (L-PFK2) to the more active ubiquitous isoform (U-PFK2). U-PFK2 converts fructose-6-phosphate to fructose-2,6-biphosphate that in turn activates the glycolytic enzyme phosphofructo-1-kinase (PFK1) and consequently increases glycolytic flux (34, 35) because of its dominant kinase activity. Since the TCA cycle is truncated in M1 macrophages, lactate production regenerates the majority of the NAD + needed to sustain glycolysis.…”
Section: Metabolic Signature Of Macrophagesmentioning
confidence: 99%